(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The pandemic has prompted an enhanced demand for a thorough interrogation regarding effective strategies of care to deal with the sanitary, social and economic crises to which it gives rise. Yet this quest for efficacious measures of recovery limits itself to the contemporary cohort of human beings and its immediate posterity, ignoring the need to extend those measures to generations in a more distant future. Such a need is justified by the simple fact that the causes of the pandemic are the multifarious anthropic activities which, far from only upsetting the planetary equilibrium for present individuals, will have a much greater impact on remote future subjects. In what follows, I first investigate the profound societal-political, and not merely contingent, reasons for such a presentistic attitude in addressing the care-issue concerning the pandemic. In a second step, I offer some considerations as to how a more future-oriented ethic of care could respond to the inescapable demand for intergenerational justice.